Brain-driven entrepreneurship research: Expanded review and research agenda towards entrepreneurial enhancement - Victor Pérez-Centeno (Institut für Mittelstandsforschung (IfM) Bonn, 2018)
The advent of significant advances in neuroscience has produced the capacity to examine the human brain at a profound level, yet the academic and practical value of existing evidence based on neuroscience techniques and methods within the field of entrepreneurship remains unexplored. To address these issues, the author draws from entrepreneurship research and presents a braindriven approach as a basis for future in-depth studies on the role of cognitive, affective, motivational and hormonal mechanisms in entrepreneurship theory and practice. To further articulate a research agenda, the author reviews the state of knowledge of existing evidence by content analysis of articles published until 2016. The analysed articles incorporate the use of a brain-driven research perspective in their studies. It is found that although neuroscience affords unique technological opportunities, few studies have thus far benefited from these advances, and among existing studies, only the topic of entrepreneurial decision-making has been partially covered. Building on these observations, the author proposes a definition of brain-driven entrepreneurship research and a research agenda to advance the integration of neuroscience tools and technologies in entrepreneurship research.
Keywords: L26; M13; O33; 330; entrepreneurial neuroscience; neuro-entrepreneurship; entrepreneurial enhancement; cognition; brain-driven entrepreneurship; entrepreneurial enhancement